Human Resource Management Practices in Nepalese Organizations: An Explanatory Study - Upreti , Mukta (Journal of Durgalaxmi, 2025)
This study explains how human resource management (HRM) practices function in Nepal and why adoption differs across sectors. It uses an explanatory qualitative design based entirely on desk research. A structured framework guided source selection, thematic coding across core HR domains, and an explanatory synthesis that links observed practices to contextual factors such as regulation, resources, leadership capability, and culture. Results show a dual trajectory. Private and joint-venture firms more often practice strategic HR planning, merit-based hiring, targeted training, and merit-linked appraisal. Public enterprises and smaller firms frequently retain administrative routines, weak planning, and formality-driven evaluations. Public bodies should insulate HR from political influence, introduce transparent succession planning, link appraisals to development and promotion, and fund regular upskilling. Private firms should deepen data-enabled talent systems and flexible job design. The paper clearly separates what is established in prior research from what is newly inferred for Nepal, using an issue-based, explanatory lens to connect sector, policy, and culture with HRM outcomes, thereby improving transparency and utility for managers and policymakers.